2019
DOI: 10.1242/dev.184218
|View full text |Cite
|
Sign up to set email alerts
|

GATA2 controls lymphatic endothelial cell junctional integrity and lymphovenous valve morphogenesis through miR-126

Abstract: Mutations in the transcription factor GATA2 cause lymphedema. GATA2 is necessary for the development of lymphatic valves and lymphovenous valves, and for the patterning of lymphatic vessels. Here, we report that GATA2 is not necessary for valvular endothelial cell (VEC) differentiation. Instead, GATA2 is required for VEC maintenance and morphogenesis. GATA2 is also necessary for the expression of the cell junction molecules VE-cadherin and claudin 5 in lymphatic vessels. We identified miR-126 as a target of GA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 71 publications
2
25
0
3
Order By: Relevance
“…PROX1, FOXC2, GATA2 and VEGFR3 are expressed at much higher levels in valvular endothelial cells compared to the rest of the lymphatic vasculature (Bazigou et al, 2009;Geng et al, 2016;Kazenwadel et al, 2015;Norrmen et al, 2009). Previous reports, including our own, have shown that PROX1, FOXC2 and GATA2 are necessary for the development of LVs and LVVs (Geng et al, 2016;Kazenwadel et al, 2015;Mahamud et al, 2019;Norrmen et al, 2009;Petrova et al, 2004). However, whether VEGFR3 is necessary for the development of valves has not been demonstrated although superficial venous valve reflex is observed in patients with Milroy's disease, which is characterized by heterozygous inactivating mutations in VEGFR3 (Mellor et al, 2010).…”
Section: Development • Accepted Manuscriptmentioning
confidence: 66%
“…PROX1, FOXC2, GATA2 and VEGFR3 are expressed at much higher levels in valvular endothelial cells compared to the rest of the lymphatic vasculature (Bazigou et al, 2009;Geng et al, 2016;Kazenwadel et al, 2015;Norrmen et al, 2009). Previous reports, including our own, have shown that PROX1, FOXC2 and GATA2 are necessary for the development of LVs and LVVs (Geng et al, 2016;Kazenwadel et al, 2015;Mahamud et al, 2019;Norrmen et al, 2009;Petrova et al, 2004). However, whether VEGFR3 is necessary for the development of valves has not been demonstrated although superficial venous valve reflex is observed in patients with Milroy's disease, which is characterized by heterozygous inactivating mutations in VEGFR3 (Mellor et al, 2010).…”
Section: Development • Accepted Manuscriptmentioning
confidence: 66%
“…On the other hand, excessive stabilization of endothelial cell junctions in mice due to covalent fusion between VE-cadherin and α-catenin strongly suppresses embryonic lymphangiogenesis (Dartsch et al, 2014), suggesting that lymphatic development critically depends on the balanced adhesive strength of zipper junctions. PROX1 (Johnson et al, 2008), RASIP1 (Liu et al, 2018), GATA2 (Mahamud et al, 2019) and miR-126 (Mahamud et al, 2019) have been identified as important regulators of VE-cadherin as well as other junction proteins in developing lymphatics. In conclusion, several lines of evidence support that VE-cadherin dynamics at adherens junctions of zippers are very important for lymphatic vessel development (Baluk et al, 2007;Yang et al, 2012Yang et al, , 2019Yao et al, 2012;Hagerling et al, 2018).…”
Section: Lec Junctions In Developmentmentioning
confidence: 99%
“…Da GATA2 eine essenzielle Rolle bei der Transkription einer Vielzahl von Genen, die an der Gefäßklappenmorphogenese beteiligt sind, spielt und somit bedeutend für die Morphogenese und Funktion der Lymphgefäßklappen ist [4,[7][8][9]14], sollten die Lymphgefäßklappen im Anschluss genauer untersucht werden.…”
Section: Resultateunclassified
“…Ferner kann durch das Fehlen der Gefäßklappen auf veränderte Flusseigenschaften in den Lymphgefäßen geschlossen werden, welches wiederum die Expression einer Vielzahl an Genen und hierdurch die Reifung der Gefäße beeinflusst [7][8][9].…”
Section: Diskussionunclassified
See 1 more Smart Citation